The Role of Prior Online Learning Experience on Student Community of Inquiry, Engagement, and Satisfaction Scores - Duha, Mohammad Shams Ud; Richardson, Jennifer C.; Maeda, Yukiko; Kucuk, Sevda (Online Learning, 2022)
The increase in online education creates a need to explore how learning outcomes, student satisfaction, and student perceptions about online courses are affected by prior online learning experiences. This study examined the role of prior online learning experience on students’ perceived cognitive presence, social presence, teaching presence, engagement, and satisfaction. The archival data of online learners at a large midwestern university (a total n=878), including survey responses related to Community of Inquiry (CoI), engagement, and satisfaction, were utilized to conduct statistical analyses to determine whether student responses differed by the number of online courses taken previously. We found that only social presence scores (CoI sub-scale) and emotional engagement scores (engagement sub-scale) differed by the number of the online courses taken. However, the effect size was small. We concluded that student satisfaction, engagement, and perceptions of cognitive and teaching presence are not related to prior online course experiences. Implications are discussed.